THE EFFECT OF DIGITAL MARKETING SKILLS AND MARKET RESEARCH ON MARKETING PERFORMANCE IN START-UP COMPANIES IN JAKARTA AND WEST JAVA, INDONESIA - Dudi Permana (Adisam Publisher, 2024)
This study looks into the relationship between marketing performance, market research use, and digital marketing expertise in start-up businesses in Jakarta and West Java, Indonesia. The study uses Structural Equation Modeling with Partial Least Squares (SEM-PLS) to quantitatively analyze 175 surveyed start-ups and investigate the correlations between these important variables. The integration of descriptive statistics, a sturdy measurement model, hypothesis testing, and model fit evaluations results in a thorough comprehension of the dynamics in the start-up ecosystem. The findings emphasize how important it is to use market research and digital marketing expertise to influence marketing performance. The findings emphasize the necessity for a comprehensive approach to digital strategy and data- driven decision-making, with practical implications for training and development programs. The present study contributes to our comprehension of the intricate variables impacting marketing efficacy within the ever-changing Indonesian startup scene.